Music Stimulation as a Method of Optimizing Autobiographical Memory in Patients Diagnosed with Alzheimer’s Disease - Ariana Ponce-Pardo; Pamela Acosta-Rodas; Jorge Cruz-Cárdenas; Carlos Ramos-Galarza (Emerging Science Journal, 2021)
Alzheimer’s is a neurodegenerative disease characterized by the progressive deterioration of cognitive functions, with memory being the most affected. Several studies have shown the benefits of music as a complementary treatment for dementia, improving patients’ quality of life. A scientific contribution is needed to show how autobiographic memory could be improved by using musical activities. Objective: The aim of this investigation is to analyze the impact of a musical stimulation protocol on the performance of autobiographical memory in elderly people suffering from Alzheimer’s. Participants and Method: This research was conducted with three patients diagnosed with Alzheimer’s disease: two females (66.7%), and one male (33.3%). One (33.3%) was in the early stages, and two were in the middle stages. This investigation used a quantitative, pre-experimental, longitudinal study with the application of two tests before and after the intervention. Findings: Changes in the performance of autobiographical memory (t=-5.79, p=0.002), and in the semantic component (t=-10.14, p=0.01) were found to be statistically significant, but no changes were evident for episodic memory (t=-0.19, p=0.86). Conclusion: This study provides preliminary evidence of the potential effectiveness of using a music protocol to improve the performance of autobiographical memory in patients with Alzheimer's Disease. Doi: 10.28991/esj-2021-01304 Full Text: PDF